2021
DOI: 10.1002/vnl.21846
|View full text |Cite
|
Sign up to set email alerts
|

Reactive processing of PA6/EPDM‐MA blends as modifier for application and development of high‐performance polypropylene

Abstract: In this work, PA6/EPDM-MA was added as an impact modifier for highperformance polypropylene (PP) production. PA6/EPDM-MA compounds were processed in an internal mixer, aiming at chemical reaction between maleic anhydride of EPDM-MA and the amine terminal groups of PA6. Afterward, PP/(PA6/EPDM-MA) blends were processed by extrusion and injection molding. Rheological properties were evaluated using torque rheometry; additionally, Fourier transform infrared spectroscopy, Molau test, impact and tensile strengths, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 85 publications
1
14
0
2
Order By: Relevance
“…Figure 5 shows the XRD diffractograms of neat PA6, PA6/SEBS-MA blend, Ni-Zn and Ni-Zn-C ferrites, and magnetic nanocomposites. It was found that neat PA6 presented a single intense peak around 2θ = 21 , indicating the predominant presence of α phase 55,56 and corroborating the FTIR results. According to the literature, 57 PA6 exhibits two dominant crystalline forms, called α and γ.…”
Section: X-ray Diffractionsupporting
confidence: 83%
“…Figure 5 shows the XRD diffractograms of neat PA6, PA6/SEBS-MA blend, Ni-Zn and Ni-Zn-C ferrites, and magnetic nanocomposites. It was found that neat PA6 presented a single intense peak around 2θ = 21 , indicating the predominant presence of α phase 55,56 and corroborating the FTIR results. According to the literature, 57 PA6 exhibits two dominant crystalline forms, called α and γ.…”
Section: X-ray Diffractionsupporting
confidence: 83%
“…PA6 and its blends showed rapid water absorption kinetics at the beginning of the experiment. The high water absorption is attributed to the hydrophilic nature of the amide groups, which favors hydrogen bonds with water [ 65 , 66 ]. After 600 h, the curve undergoes a smooth change in slope, reaching a linear and stable level.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the crystals began to melt prematurely, reinforcing the suggestion of smaller or less perfect crystals. [86] Figure 14A,B presents the crystallization rate and relative crystallinity of BioPE and its biocomposites, respectively. In general, the biocomposites exhibited a higher crystallization rate, that is, the crystals crystallize quicker when compared to neat BioPE.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%